Energy metabolism in cardiovascular diseases: unlocking the hidden powerhouse of cardiac pathophysiology - Chen, Li; Chen, Mingtai; Yang, Xinrui; Hu, Yuanli; Qiu, Caiwei; Fu, Youyou; Lan, Xiaoyu; Luo, Gang; Liu, Qiuyu; Liu, Mengnan (Frontiers in Endocrinology, 2025)
Cardiovascular diseases (CVDs) remain the leading cause of global mortality, yet their pathogenesis has not been fully elucidated, particularly regarding the role of abnormal energy metabolism. Major outstanding questions pertain to the dynamic regulation of metabolic reprogramming and its complex interplay with mitochondrial dysfunction. Previous studies have demonstrated that the heart, as a high-energy-demand organ, relies on the dynamic equilibrium of substrates such as fatty acid (FA) and glucose to sustain adenosine triphosphate (ATP) production. Metabolic disturbances—characterized by suppressed FA oxidation and aberrant activation of glycolysis—directly contribute to the pathological progression of various CVDs, including heart failure (HF), atherosclerosis, and myocardial infarction(MI), through mechanisms involving oxidative stress, inflammatory responses, and an energy crisis. This review systematically examines the core pathways of cardiac energy metabolism (e.g., mitochondrial oxidative phosphorylation (OXPHOS), regulation of glucose and lipid metabolism) and their dysregulation in disease states, while evaluating intervention strategies targeting metabolic pathways, such as mitochondrial function enhancement and substrate utilization modulation. Future research directions emphasize the integration of metabolomics with clinical translational studies to comprehensively decipher the multidimensional regulation of metabolic networks, thereby facilitating the development of novel precision therapeutic targets.